Correction: Environmental regulation, green innovation, and international competitiveness of manufacturing enterprises in China: From the perspective of heterogeneous regulatory tools. - Yuanhong Hu; Sheng Sun; Yixin Dai (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0249169.].